2021
DOI: 10.1093/biolre/ioab045
|View full text |Cite
|
Sign up to set email alerts
|

Reversing complete mechanical transzonal projections disruption during mouse in vitro follicle culture with unaltered oocyte competence

Abstract: In vitro oocyte growth is widely studied as an alternative fertility preservation approach. Several animal models are used to generate extensive information on this complex process regulated by the constant and dynamic interaction between the oocyte and its somatic compartment throughout follicle growth and maturation. A 2-dimensional (2D) attachment mouse secondary follicle culture system was used to assess the oocyte’s capacity to overcome disconnection from its somatic companions at different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…Once the oocyte reaches full-size, it acquires the ability to undergo the final stage of development, termed meiotic maturation, but is prevented from precociously doing so by cyclic GMP that is produced and transferred to it by the granulosa cells, also via gap junctions (Jaffe & Egbert, 2016 ;Norris et al, 2009 ;Zhang et al, 2010 ). In vitro, oocytes can develop normally when enclosed by granulosa cells but not when the granulosa cells are removed and provided in co-culture, further emphasizing the crucial importance of physical contact between the two cell types (Eppig, 1979 ;Herta et al, 2021 ;O'Brien et al, 2003 ).…”
Section: Sent For Peer Reviewmentioning
confidence: 99%
“…Once the oocyte reaches full-size, it acquires the ability to undergo the final stage of development, termed meiotic maturation, but is prevented from precociously doing so by cyclic GMP that is produced and transferred to it by the granulosa cells, also via gap junctions (Jaffe & Egbert, 2016 ;Norris et al, 2009 ;Zhang et al, 2010 ). In vitro, oocytes can develop normally when enclosed by granulosa cells but not when the granulosa cells are removed and provided in co-culture, further emphasizing the crucial importance of physical contact between the two cell types (Eppig, 1979 ;Herta et al, 2021 ;O'Brien et al, 2003 ).…”
Section: Sent For Peer Reviewmentioning
confidence: 99%
“…Two types of TZPs, distinguished by the major cytoskeletal component that constitutes their backbone, have so far been described. Most TZPs contain F‐actin, as revealed by the dense network that is observed in numerous mammals when preparations are stained using phalloidin, a cyclic heptapeptide that binds to filamentous (F)‐actin (Figure 4a) (Albertini & Rider, 1994; Allworth & Albertini, 1993; Barrett & Albertini, 2010; Barrett et al, 2010; Carabatsos et al, 1998; De Smedt & Szollosi, 1991; Herta et al, 2021; Macaulay et al, 2014; Makita & Miyano, 2014; Yuan et al, 2017). Actin‐TZPs also contain proteins that are typically found in filopodia.…”
Section: Tzp Basicsmentioning
confidence: 99%
“…Most obviously, as noted earlier, the number of TZPs that emanate from one granulosa cell is much greater than the number of filopodia of the same cell that are not oriented toward the oocyte (Baena & Terasaki, 2019). In addition, when the oocyte was removed from follicles growing in vitro and deposited on top of the remaining follicular somatic cells, the oocyte became reintegrated into the follicle (Herta et al, 2021). TZPs connected the two cell types, implying that new TZPs to be formed following re‐integration, similar to the reaggregation studies described above.…”
Section: How Are Tzps Generated?mentioning
confidence: 99%
“…On culture day 9, the oocyte-somatic reconnection rate, the presence of transzonal projections (TZPs), and oocyte growth were assessed; on day 10, after hCG/EGF stimulation, oocyte maturation rate was assessed and developmental competence was studied by in vitro fertilization (IVF) and gene expression analysis. The results of the study indicated that in vitro grown oocytes can reconnect with their somatic companions if isolated at preantral and early antral stages, with no impact on follicle morphology and oocyte competence [ 28 ]. These novel findings constitute good premises for developing successful strategies to rescue human oocyte competence in the context of biphasic IVM.…”
Section: In Vitro Maturation Of Oocytesmentioning
confidence: 99%